Study of The Drying on The Pore Network in order to Comparison of the Phase Distribution between Measured and Simulated Results - Tran, Quoc Tiep; Ta, Hong Duc (Old Journal, 2018)
Non-isothermal drying processes are empirical studied on the pore network at the different temperature gradients. Their results have been compared with a corresponding mathematical model. To conduct the empirical experiment, a pore network with 50x50 pores, are created by electron lithography method. The temperature distribution from the top to the bottom of the network is determined by an infrared camera and then these results are adopted in the mathematical model algorithm. During the drying process, the series of images showing the phase change in network is observed and recorded, which will be processed with an algorithm built in MATLAB. From that, we find out the change of network saturation, drying rate and the increase in the number of clusters and in the size of the main cluster in network. The phase distribution in the experiment is consistent with the simulation results at different temperature gradients.